Pre-school Teachers’ Beliefs towards Their Abilities of Teaching English to Pre-schoolers in Pahang, Malaysia - Aisyah Khaleeda, Rosli; Noor Raha, Mohd Radzuan (LPPM Universitas Pahlawan Tuanku Tambusai, 2020)
Recent studies have revealed that English has become a global language that is commonly used, particularly in the education sector, for various purposes. In the education sector, teachers serve as the most important role model in improving learners’ English language competency. Evidently, at the age of 4 to 6 years old, preschoolers are proven to be able to learn a second language sufficiently hence it is critical for pre-school teachers to be able to teach English to the children at this stage precisely. English, however, is not set to become one of the major requirements for pre-school teachers, especially in Pahang, Malaysia. Due to this, the beliefs of the pre-school teachers initiate a critical indicator in deciding if, given the circumstances, pre-school children can receive adequate English inputs and exposure at their age. The aim of this study is to identify the beliefs of pre-school teachers in their ability of teaching English to preschoolers in Pahang, Malaysia. In the study, 60 pre-school teachers in Pahang were given a set of questionnaires consisting of 14 items and all 60 were returned. In the pilot study, the questionnaire showed a 0.9 Cronbach alpha value indicating a high reliability point. The findings of this study suggest a much more positive view of teachers’ beliefs in pre-school English teachings. This can become a stimulus for the growth of English proficiency among Malaysian children and consequently improve the standard of English in Malaysia in the future.